2022
DOI: 10.1200/jco.21.01667
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Randomized, Phase III Trial of Short-Term Radiotherapy Plus Chemotherapy Versus Long-Term Chemoradiotherapy in Locally Advanced Rectal Cancer (STELLAR)

Abstract: PURPOSE To ascertain if preoperative short-term radiotherapy followed by chemotherapy is not inferior to a standard schedule of long-term chemoradiotherapy in patients with locally advanced rectal cancer. MATERIALS AND METHODS Patients with distal or middle-third, clinical primary tumor stage 3-4 and/or regional lymph node–positive rectal cancer were randomly assigned (1:1) to short-term radiotherapy (25 Gy in five fractions over 1 week) followed by four cycles of chemotherapy (total neoadjuvant therapy [TNT])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
211
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(224 citation statements)
references
References 34 publications
9
211
1
3
Order By: Relevance
“…The randomized Swedish trial, Stockholm III trial, which tested “SCRT followed by delayed surgery,” showed that the downstaging effects of SCRT were similar to those of LCRT [ 25 ]. Furthermore, several recent trials, such as the Radiotherapy And Preoperative Induction therapy followed by Dedicated Operation (RAPIDO) and the Short Term radiotherapy followed by chEmotherapy versus Long-term chemoradiotherapy in Locally Advanced Rectal cancer (STELLAR) trial which integrated SCRT into TNT strategy, showed outcomes that were promising or at least comparable with those of standard LCRT [ 24 , 26 ]. These studies demonstrated that when the time interval between SCRT and surgery is delayed, SCRT seems to have outcomes comparable with LCRT.…”
Section: Discussionmentioning
confidence: 99%
“…The randomized Swedish trial, Stockholm III trial, which tested “SCRT followed by delayed surgery,” showed that the downstaging effects of SCRT were similar to those of LCRT [ 25 ]. Furthermore, several recent trials, such as the Radiotherapy And Preoperative Induction therapy followed by Dedicated Operation (RAPIDO) and the Short Term radiotherapy followed by chEmotherapy versus Long-term chemoradiotherapy in Locally Advanced Rectal cancer (STELLAR) trial which integrated SCRT into TNT strategy, showed outcomes that were promising or at least comparable with those of standard LCRT [ 24 , 26 ]. These studies demonstrated that when the time interval between SCRT and surgery is delayed, SCRT seems to have outcomes comparable with LCRT.…”
Section: Discussionmentioning
confidence: 99%
“…In the RAPIDO trial, higher pCR rates translated to improved DFS and lower incidence of distant metastasis [ 10 ]. In the PRODIGE-23 trial, pCR, TRG 4 and low-risk NAR score in the TNT arm correlated with improved DFS, whereas in the STELLAR trial, improved pCR was not associated with better DFS [ 12 , 13 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike pCR, TRG and the NAR score classifies tumor response more gradually beyond a simple binary system that may reflect treatment efficacy better and may have a greater ability than pCR to predict DFS or OS, as proposed by Yothers et al [ 4 , 35 ]. Even if the surrogacy of TRG and NAR for improved DFS has been validated in the CAO/ARO/AIO-04 trial [ 16 , 17 ] and a significant trend to higher tumor regression and low NAR score correlated with improved DFS and lower incidence of distant metastasis in the PRODIGE-23 trial [ 12 ], potential surrogacy of both parameters has not been broadly reported in recent trials ( Table 4 ) [ 10 , 13 , 14 ]. Furthermore, assessment and reporting of TRG is heterogeneous, and no universally approved standardization method is accepted [ 4 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the STELLAR study, 4 the 3-year cumulative incidence of locoregional recurrence of 8.4%-11.0% and 3-year DFS of 62.3%-64.5% were reasonable because of the inclusion of more patients with adverse clinical factors, such as middle low location only, more positive EMVI (47.9%), and MRF (56.3%). The STELLAR and Polish II trials only included patients with middle low rectal cancer, 4,6 whereas the RAPIDO and PRODIGE trials included patients with all sites of rectal cancer, with upper rectal cancer of 33% and 13%. 5,7 Moreover, approximately half patients (49.2%) in the STELLAR study had disease localized in low rectal cancer, which were slightly lower than 55.5% in the Polish II trial, but significantly higher than 23.9% in the RAPIDO trial and 36.9% in the PRODIGE trial, leading to a large proportion of our patients (43.2%) treated with abdominoperineal resection.…”
mentioning
confidence: 99%